PENAZAMAN HADIS TENTANG AL-QUR’AN (Kajian Kitab al-Masabih an-Nuraniyyah fi al-Ahadis al-Qur’aniyyah Karya KH Abdullah Umar) - Baidowi, Ahmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
; ">This article is trying to dwell upon a subject about an Indonesian opuswhich could be categorized into Koranic and Hadith Studies, that is alMaá¹£Äbiá¸¥ al-NÅ«rÄniyah f Naáº“m al-Aá¸¥ÄdÄ«s al-Qurâ€™Äniyyah, by K.H. AbdullahUmar al-Hafiz (1929-2001). He were a well-known muslim scholar inKoranic Studies particularly for Islamic Boarding School communities inSemarang. His effort in helping forward the education on Koranic studieswere recognized in several regions in Indonesia as well as to the nearestneighboring countries. Al-Maá¹£Äbiá¸¥ al-NÅ«rÄniyah f Naáº“m al-Aá¸¥ÄdÄ«s alQurâ€™Äniyyah is unique, it comprises with poems of Prophet Muhammadâ€™shadiths that consist of all objects about Koran especially related to theposition of Koran, the virtues of memorizing, and reading it. There are53 palindromes of poem, each of 2 poems are a prelude which consist ofapprobation to Allah and invocation to the Prophet. While the rest of thebook is the chapter â€œFad} a>â€™il al-Qurâ€™a>nâ€œ (The virtues of Koran) amountingabout 51 poem palindromes. Each of them is translated row by row andwas used for a traditional translating in traditional Islamic boardingschools. The purpose of this practice is to get a language learning, eithernahwu, saraf or vocabularies mastering.